Recent developments in planetary Aeolian studies and their terrestrial analogs - BOURKE, MARY (My University, 2013)
This paper summarizes the many advances that have been made in the study of planetary Aeolian processes that have taken place since the first Planetary Dunes Workshop was held in May of 2008, through 2011. Many of the recent studies are facilitated by the wealth and variety of high resolution imaging and spectra data still being returned by multiple spacecraft in orbit and on the surface of Mars, as well as Cassini radar and imaging data for the unique linear dunes on Titan, the large moon of Saturn. The report is divided into seven broad topics: exploring the Martian rock record, the action of the wind, sediment composition, sediment transport, Aeolian bedforms, modification processes, and Titan. Analog studies of terrestrial landforms and processes continue to improve our understanding of the operation of Aeolian processes on other planetary surfaces in each of these topics. Four subjects are likely to see increased emphasis during the coming years: Martian aeolianites, sand compositional diversity, active versus inactive features, and deposition versus erosion. Continued growth of the planetary Aeolian literature is expected as several spacecraft continue to provide high-quality data, including the successful arrival of the Curiosity rover at Mars in August of 2012.
PUBLISHED
Keywords: planetary; geomorphology; aeolian; mars; Smart & Sustainable Planet